Ticagrelor plus aspirin versus clopidogrel plus aspirin for platelet reactivity in patients with minor stroke or transient ischaemic attack: open label, blinded endpoint, randomised controlled phase II trial. (5th June 2019) - Wang, Yilong; Chen, Weiqi; Lin, Yi; Meng, Xia; Chen, Guohua; Wang, Zhimin; Wu, Jialing; Wang, Dali; Li, Jianhua; Cao, Yibin; Xu, Yuming; Zhang, Guohua; et al.
Abstract: Objective: To test the hypothesis that ticagrelor plus aspirin is safe and superior to clopidogrel plus aspirin for reducing high platelet reactivity at 90 days and stroke recurrence in patients with minor stroke or transient ischaemic attack, particularly in carriers of the CYP2C19 loss-of-function allele and patients with large artery atherosclerosis. Design: Open label, blinded endpoint, randomised controlled phase II trial. Setting: Prospective studies conducted at 26 centres in China, August 2015 to March 2017. Participants: 675 patients with acute minor stroke or transient ischaemic attack. Intervention: Ticagrelor (180 mg loading dose, 90 mg twice daily thereafter) or clopidogrel (300 mg loading dose, 75 mg daily thereafter) on a background of aspirin (100 mg daily for the first 21 days) within 24 hours of symptom onset. Main outcome measures: Primary outcome was the proportion of patients with high platelet reactivity at 90 days. High platelet reactivity was defined as P2Y12 reaction units of more than 208. Secondary outcomes included high platelet reactivity at 90 days (7 days either way) in patients carrying genetic variants that would affect clopidogrel metabolism, and any stroke (ischaemic or haemorrhagic) recurrence at 90 days (7 days either way), six months, and one year. Results: At 90 days, high platelet reactivity occurred in 35 (12.5%) of 280 patients in the ticagrelor/aspirin group and 86 (29.7%) of 290 patients in the clopidogrel/aspirin group (risk ratio 0.40; 95% confidence interval 0.28 to 0.56; P<0.001), and in 10.8% versus 35.4% (0.31; 0.18 to 0.49; P<0.001) of patients carrying CYP2C19 loss-of-function alleles. Stroke occurred in 21 (6.3%) of 336 patients in the ticagrelor/aspirin group and 30 (8.8%) of 339 patients in the clopidogrel/aspirin group (hazard ratio 0.70; 95% confidence interval 0.40 to 1.22; P=0.20). Patients with large artery atherosclerosis in the ticagrelor/aspirin group had a lower stroke recurrence at 90 days than those in the clopidogrel/aspirin group (6.0% v 13.1%; hazard ratio 0.45, 95% confidence interval 0.20 to 0.98; P=0.04). No difference was seen in the rates of major or minor haemorrhagic events between the ticagrelor/aspirin and clopidogrel/aspirin groups (4.8% v 3.5%; P=0.42). Conclusion: Patients with minor stroke or transient ischaemic attack who are treated with ticagrelor plus aspirin have a lower proportion of high platelet reactivity than those who are treated with clopidogrel plus aspirin, particularly for those who are carriers of the CYP2C19 loss-of-function allele. The results of this study should be evaluated further in large scale, phase III trials and in different populations. Trial registration: Clinicaltrials.gov NCT02506140 .